Determinant Pertumbuhan Laba pada Bank yang Terdaftar di BEI - Muhammad Kadafi; E. Retno Maninggarjati; Khairul Adi Saputra (Jurnal EKSIS, 2022)
This study aims to determine is an effect of financial ratios on the growth of bank profits listed on the IDX for the 2018-2020 period. This study is a quantitative study with secondary data obtained from the annual financial statements of banks listed on the IDX with a total bank population of 10 with a period of 3 years from 2018-2020 and the number of samples collected as many as 30 samples. This study uses multiple linear regression analysis. The results show the results of the t-test of the Loan to Deposit Ratio variable with t count of -3.461 < 2.0639 and a significance value of 0.002 < 0.05. This proves that the Loan to Deposit Ratio variable partially has a negative and significant effect on the growth of bank profits listed on the IDX in 2018-2020. And for the variables Return On Assets, Return On Equity, Net Interest Margin and Capital Adequacy Ratio are partially not significant effect on profit growth, the significance value is greater than 0.05. Simultaneous test results are the results of the f test obtained that the calculated f value is greater than f table with a value of 3.223 > 2.60 and a significance value that is smaller than 0.05, namely 0.023. So it can be concluded that the variables Loan to Deposit Ratio, Return On Assets, Return On Equity, Net Interest Margin and Capital Adequacy Ratio simultaneously affect the growth of bank profits listed on the IDX.